KRESS, Gunther R. (2010). Multimodality: A Social Semiotic Approach to Contemporary Communication - Ezquerra, Julian E. (Revista Latinoamericana de Estudios del Discurso, 2020)
KRESS, Gunther R. (2010). Multimodality: A Social Semiotic Approach to Contemporary Communication. London & New York: Routledge. 213 pp. ISBN 978-0-415-32061-0.